An effective members-adding method for truss topology optimization based on principal stress trajectories. Issue 6 (7th August 2017) - Gao, Ge; Li, Yaobin; Pan, Hui; Chen, Limin; Liu, Zhenyu
Abstract : Purpose: The purpose of this paper is to provide an effective members-adding method for truss topology optimization in plastic design. Design/methodology/approach: With the help of the distribution of principal stress trajectories, obtained by finite element analysis of the design domain, ineffective zones for force transmission paths can be found, namely, areas whose nodes may have ersatz nodal displacements. Members connected by these nodes are eliminated and the reduced ground structure is used for optimization. Adding members in short to long order and limiting the number of members properly with the most strained ones added, large-scale truss problems in one load case and multiple-load cases are optimized. Findings: Inefficient members (i.e. bars that fulfil the adding criterion but make no contribution to the optimal structure) added to the ground structure in each iterative step are reduced. Fewer members are used for optimization than before; therefore, faster solution convergence and less computation time are achieved with the optimized result unchanged. Originality/value: The proposed members-adding method in the paper can alleviate the phenomenon of ersatz nodal displacements, enhance computational efficiency and save calculating resources effectively.